ANALISIS PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN PADA WARUNG AYAM PENYET BAROKAH - Syahab, Muhammad Asyari; Yanti, Aprilda (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
The development of the culinary business has experienced quite rapid development. The main factor in the development of this culinary business is the support in the form of tourism, which is now starting to gain attention. Apart from this, the culinary business is a choice for entrepreneurs because the uniqueness it brings is able to attract the younger generation to consume it. One of the culinary businesses is Ayam Penyet which is much sought after by the people of Medan. The aim of this research is to analyze the influence of product quality on customer satisfaction at the